Davida Harveya koncepcja prawa do miasta. Pomiędzy odzyskiwaniem a przebudową wielkich aglomeracji - Piskozub, Piotr (Uniwersytet Wrocławski. Wydział, Prawa, Administracji i Ekonomii, 2013)
The main goal of the article is to discuss the concepts of „right to the city” and „urban revolution” formulated by David Harvey. The author poses a question how can a city be more socially just when it comes to the access of individuals or groups to the resources of the city. According to the author the „right to the city” may be today one of the most valuable but at the same time one of the most neglected human rights. The paper is also intended to serve as an educational tool in the debate on major determinants of urbanization.
Keywords: Harvey, David; metropolizacja; prawo do miasta